2021
DOI: 10.1590/1982-4327e3112
|View full text |Cite
|
Sign up to set email alerts
|

Predictor Variables of Childbearing Motivations in Brazilian Women and Men

Abstract: This study aimed to analyze the relationships between positive (PCM), negative (NCM) childbearing motivations and psychological, sociodemographic, family of origin and partner relationship variables in a sample of 1969 Brazilians (83.6% female), aged 18 to 50 years (M = 29.27; SD = 5.97). Spearman correlations, Mann-Whitney and Kruskal Wallis U-tests, and multiple regressions were performed. The results of the correlations and multiple regressions verified the relationship between both motivations and the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Motivação é um conceito amplamente usado Aspectos da Transmissão Psíquica Sobre o Desejo de Ter Filhos: Um Estudo Teórico -Jaqueline da Silva Moraes Revista Brasileira de Terapia Familiar, 11(1), julho 2022 28 dentro da psicologia e, para melhor compreensão do nosso trabalho, definiremos as motivações como aspectos psicológicos ou disposições latentes que percebem de modo favorável ou desfavorável ter ou não ter filhos (Miller, Severy & Pasta, 2004). Desse modo, a motivação atua como força motriz por trás da intenção reprodutiva, e só adquire um caráter energizante quando interposta pelos aspectos psicológicos e comportamentais (Varas & Borsa, 2021).…”
Section: Introductionunclassified
“…Motivação é um conceito amplamente usado Aspectos da Transmissão Psíquica Sobre o Desejo de Ter Filhos: Um Estudo Teórico -Jaqueline da Silva Moraes Revista Brasileira de Terapia Familiar, 11(1), julho 2022 28 dentro da psicologia e, para melhor compreensão do nosso trabalho, definiremos as motivações como aspectos psicológicos ou disposições latentes que percebem de modo favorável ou desfavorável ter ou não ter filhos (Miller, Severy & Pasta, 2004). Desse modo, a motivação atua como força motriz por trás da intenção reprodutiva, e só adquire um caráter energizante quando interposta pelos aspectos psicológicos e comportamentais (Varas & Borsa, 2021).…”
Section: Introductionunclassified
“…Despite the fact that there are various studies that relate the TDIB model to various variables such as politics (Liu et al, 2023), fatal diseases (Buber-Ennser et al, 2023;Djiometio et al, 2019;Guo et al, 2022), race (Alexander et al, 2021), couple relationship (Barber et al, 2019), among others; empirical evidence of family of origin characteristics as predictors of CM in the national and international literature is scarce (Rich et al, 2021;Varas & Borsa, 2021). Gerson (1980Gerson ( , 1983Gerson ( , 1984Gerson ( , 1986, assessed the impact on CM of perceived parental attention, parental identification, and happiness of family life in childhood and the results indicated that CMs are correlated with the aforementioned variables.…”
mentioning
confidence: 99%